The Influence of Education Expenditures, Health Expenditures, Social Assistance Expenditures, and Per Capita Income on the Regency/City Human Development Index In South Kalimantan Province - Zulkarnain*, Zulkarnain; Muzdalifah, Muzdalifah; Yunani, Ahmad (Riwayat: Educational Journal of History and Humanities, 2024)
This research aims to determine and analyze the influence of Education Expenditure, Health Expenditure, Social Assistance Expenditure, and Per Capita Income partially and simultaneously on the human development index in 13 districts/cities of South Kalimantan Province. This type of research is quantitative. Regression analysis using panel data is a combination of time series data for the 2018-2022 period. The results show that education spending and per capita income have a positive and significant effect on the human development index in South Kalimantan Province. Health spending and social assistance spending have a positive and insignificant effect on the human development index in South Kalimantan Province. Education Expenditure, Health Expenditure, Social Assistance Expenditure, and Per Capita Income simultaneously have a significant effect on the human development index in South Kalimantan Province